Penerapan Metode Picture And Picture Dengan Media Cerita Gambar Berseri Terhadap Kemampuan Bahasa Pada Anak Kelompok B - Aris Suziman (Prodi PGSD Unsultra, 2022)
This study aims to develop children’s language skills through the implementation of the Picture and Picture method using serial picture story media. This research is a collaborative Classroom Action Research (CAR) employing the Asrori M. model. Each cycle consists of four stages: planning, implementation, observation, and reflection. The research subjects were 13 children from Group B of TK Beringin Jaya, while the object of the study was the development of children’s language skills through the Picture and Picture method using serial picture stories. Data collection techniques included observation and performance tests. The observation instrument consisted of an observation sheet containing 10 aspects, while performance tests were conducted at the end of each cycle to measure learning outcomes according to the targeted indicators. The results showed that children’s language ability improved significantly through the implementation of the Picture and Picture method with serial picture story media. In Cycle I, out of 13 children, 1 child (7.69%) was in the Not Yet Developed (NYD) category, 3 children (15.38%) in the Beginning to Develop (BD) category, 5 children (38.46%) in the Developing as Expected (DAE) category, and 4 children (30.76%) in the Very Well Developed (VWD) category. In Cycle II, 1 child (7.69%) remained in the NYD category, 1 child (7.69%) in BD, 6 children (46.15%) in DAE, and 5 children (38.46%) in VWD. The average score of children’s language ability reached 84.61%, exceeding the mastery standard set by TK Beringin Jaya.